2019
DOI: 10.1186/s12911-018-0729-0
|View full text |Cite
|
Sign up to set email alerts
|

Replicating medication trend studies using ad hoc information extraction in a clinical data warehouse

Abstract: BackgroundMedication trend studies show the changes of medication over the years and may be replicated using a clinical Data Warehouse (CDW). Even nowadays, a lot of the patient information, like medication data, in the EHR is stored in the format of free text. As the conventional approach of information extraction (IE) demands a high developmental effort, we used ad hoc IE instead. This technique queries information and extracts it on the fly from texts contained in the CDW.MethodsWe present a generalizable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Our approach should be seen as a support for standard clinical studies. Conventional studies can, e.g., be motivated by such results or the results of conventional studies can be confirmed by research based on reused routine data [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our approach should be seen as a support for standard clinical studies. Conventional studies can, e.g., be motivated by such results or the results of conventional studies can be confirmed by research based on reused routine data [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…While this review was not systematic, our comprehensive approach returned over 2000 articles by PubMed search criteria of which 128 articles were reviewed in detail. The key studies worth highlighting from this search include: 1) PEEP (phenotype extraction in epilepsy) which is highly accurate for medication dosing and extracts key information regarding epileptogenic zone, etiology, semiology and EEG patterns from EMU discharge summaries [9,10] and 2) ExECT (extraction of epilepsy clinical text) which extracts epilepsy diagnosis, epilepsy type, abnormal findings on imaging, and seizure frequency (albeit with some limitations) [28]. However, great variability in algorithm performance across variables persists.…”
Section: Discussionmentioning
confidence: 99%
“…The best pipeline for extraction of active medication ingredients and dosing achieves greater than 97 % F1s [9,10]. However, extracting the indication for each medication is more difficult, with the best group achieving F1 of 66 % [11].…”
Section: Exposure Variables 311 Medicationmentioning
confidence: 99%
“…[6,8] The best pipeline for extraction of active medication ingredients and dosing achieves greater than 97% F1s. [9,10] However, extracting the indication for each medication is more difficult, with the best group achieving F1 of 66%. [11] Extracting the indication is particularly important in the field of epilepsy, since many of our medications may be prescribed for alternative indications (e.g.…”
Section: Medicationmentioning
confidence: 99%